Beyond the Chinese connection : contemporary Afro-Asian cultural production - Anderson, Crystal S. (Jackson : University Press of Mississippi, 2013)
In Beyond The Chinese Connection, Crystal S. Anderson explores the cultural and political exchanges between African Americans, Asian Americans, and Asians over the last four decades. To do so, Anderson examines such cultural productions as novels (Frank Chin's Gunga Din Highway [1999], Ishmael Reed's Japanese By Spring [1992], and Paul Beatty's The White Boy Shuffle [1996]); films (Rush Hour 2 [2001], Unleashed [2005], and The Matrix trilogy [1999-2003],) and Japanese animation (Samurai Champloo [2004]), all of which feature cr
Afro-Asian cultural production and the rise of the global culture -- "You can stay at my crib, I will show you my 'hood": Interethnic male friendship -- "Scheming, treacherous, and out for revenge": Ethnic imperialism -- "Some things never change, and some things do": Interethnic conflict and solidarity.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Asian Americans in literature; Asian Americans in motion pictures; Asian Americans in popular culture; African Americans in literature; African Americans in motion pictures; African Americans in popular culture; Asians in mass media; African Americans -- Relations with Asian Americans; SOCIAL SCIENCE / Ethnic Studies / Asian American Studies; Electronic books